Dukungan sosial bagi penderita lupus: Dapatkah menjadi moderator bagi efek penerimaan diri terhadap rasa syukur? - Ayumi Nalikrama Dienillah; Sitti Chotidjah (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2021)
Social support contributes to Lupus patients in the process of treating their diseases. The condition of lupus sufferers who experience various physical changes can affect their psychological state. Social support sometimes does not have a positive influence, but it can also have a negative effect. This study aims to see whether social support can moderate self-acceptance and gratitude for lupus sufferers. Participants in this study were 206 lupus sufferers. The results showed that social support can moderate self-acceptance and gratitude. The results were then discussed.